(untitled) (ESMAT Magazine, 2020)
How to explain some efforts to create a special criminal law’s provisions in economic and financial matter, in particular in criminal procedure? It is possible to reveal two hypothetical logics: the logic of Crime Control, according to which the criminal law has to become more efficient for fighting the economic and financial criminality, and the logic of Doing Business,according to which the criminal law almost has to disappear from the economic sphere not to disturb the economic activity. The Russian criminal law is actually an example of the Doing Business criminal policy’s movement, which brings more problems than positive results. It follows that the Doing Business logic cannot be a criminal policy’s principle in economic and financial matter.